A highly effective antibacterial porous electrospun nanofiber and its preparation method and application

The porous nanocomposite fiber material embedded with hydrogen bonded organic framework materials was prepared by electrospinning, which solved the problems of low mechanical strength and insufficient light and oxygen utilization efficiency in practical applications of hydrogen bonded organic framework materials, and achieved efficient bacteria, virus and fungal killing effects.

CN116427049BActive Publication Date: 2025-03-25FUDAN UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310068529.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-06
Publication Date
2025-03-25
Estimated Expiration
2043-02-06

AI Technical Summary

Technical Problem

In practical applications, the existing hydrogen bond organic framework coatings have problems such as low mechanical strength, easy peeling, and insufficient light and oxygen utilization efficiency.

Method used

Nanofibers with polyvinylidene fluoride or polyvinylidene fluoride total hexafluoropropylene as the main body are prepared by electrospinning, and porous hydrogen bonded organic framework material monomers, such as tetrakis(parabenzoic acid)pyrene or 1,3,6,8-tetrakis(2-fluoro-4-carboxybenzene)pyrene are embedded to form porous nanocomposite fiber materials.

Benefits of technology

The stability and mechanical strength of hydrogen bonded organic framework materials are improved, the production rate of singlet oxygen under light conditions is enhanced, and the killing efficiency of bacteria, viruses and fungi is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116427049B_ABST
    Figure CN116427049B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of porous composite nanomaterials, specifically a kind of antibacterial porous electrostatic spinning nanofiber and its preparation method and application. The present invention uses polymer material polyvinylidene fluoride or polyvinylidene fluoride co-hexafluoropropylene as the fiber body, embeds porous hydrogen-bonded organic skeleton material monomer tetrakis (tert-butyl) pyrene or 1,3,6,8-tetrakis (2-fluoro-4-carboxyphenyl) pyrene, and forms a porous nano composite fiber material; The nano fiber material has porosity, high mechanical strength and good air permeability, and can generate singlet oxygen in situ under illumination conditions, and its singlet oxygen generation rate is 2 times that of hydrogen-bonded organic skeleton micron crystals; The nano fiber material can efficiently kill bacteria, viruses and fungi under illumination conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of porous composite nanomaterials, and specifically relates to an antibacterial porous electrostatic spinning nanofiber and a preparation method and application thereof. Background Art

[0002] Antibiotics are a solution for treating bacterial or fungal infections, but the misuse of antibiotics can lead to the evolution of threatening drug-resistant bacteria, so it is very important to find or develop new antibacterial strategies. Some materials commonly used to replace antibiotics, such as silver nanoparticles or quaternary ammonium compounds, have certain limitations. Fortunately, reactive oxygen species are a class of highly efficient and environmentally friendly bactericidal substances that are widely used in medical and antibacterial fields and do not lead to drug resistance. Photoactive materials that can generate reactive oxygen species are inexpensive, easy to use and reusable, and have a wide range of application scenarios. Nanoparticles of graphitic carbon nitride or metal oxides, such as titanium dioxide and zinc oxide, can generate various types of reactive oxygen species under ultraviolet irradiation, but continuous illumination is required, and the zinc (II) ions released by zinc oxide nanoparticles have been found to be toxic to humans. Recently, hydrogen-bonded organic framework materials have emerged as porous materials with a wide range of applications, including gas adsorption and separation, catalysis, sensing, and biomedicine. Hydrogen-bonded organic framework materials that generate and store reactive oxygen species under light have been used as photoactive porous molecular coatings for long-term antibacterial effects.

[0003] However, there are many limitations in the practical use of hydrogen-bonded organic framework material coatings: First, drop casting on the material surface relies on the physical interaction between the coating and the support, which results in low mechanical strength of the composite material and the hydrogen-bonded organic framework coating is easily peeled off during cleaning; Second, since the efficiency of oxygen conversion to singlet oxygen is much higher than the adsorption rate of oxygen under irradiation, most of the singlet oxygen is generated only on the surface of the hydrogen-bonded organic framework material, which leads to insufficient utilization of light and oxygen by micron-scale hydrogen-bonded organic framework materials.

[0004] Therefore, we expect to increase the hydrogen bonding interaction between the hydrogen-bonded organic framework material and the load material to improve the stability of the hydrogen-bonded organic framework material in practical applications. In addition, selecting a load material of sufficient strength can greatly improve the flexibility of the composite material. Selecting a load material of sufficient strength can greatly improve the flexibility of the composite material. Polymer flexible fiber materials are good carriers that can replace ordinary fibers, and solvent processability makes hydrogen-bonded organic framework materials very suitable for processing with polymer fiber materials. In addition, a feasible way to further improve the efficiency of active oxygen production is to replace micron-sized hydrogen-bonded organic framework material particles with nanocrystals. The traditional method of adjusting the crystal size of hydrogen-bonded organic framework materials is to use different solvents, but this method is not universally applicable to all hydrogen-bonded organic framework materials.

[0005] Electrospinning is the main production technology of polymer-based nanofiber components, which has the advantages of simplicity and low cost. Electrospun nanofibers have been widely used in adsorption and separation, catalysis, energy storage, sensors, biomedicine, etc. With the continuous development of devices, batch manufacturing of electrospun nanofibers with diameters ranging from tens of nanometers to tens of microns can be achieved. Electrospun composite nanofibers composed of polymers and hydrogen-bonded organic skeleton materials will increase the stability of hydrogen-bonded organic skeleton materials through the embedding effect and adjust the size of hydrogen-bonded organic skeleton materials through the closing effect.

[0006] The present invention has developed an electrospinning synthesis method for preparing a series of antibacterial nanofibers using a hydrogen-bonded organic skeleton material and a solution of polyvinylidene fluoride co-hexafluoropropylene. The content of the hydrogen-bonded organic skeleton material in the nanofibers is adjustable and can efficiently kill bacteria, viruses and fungi under light conditions. Summary of the invention

[0007] The purpose of the present invention is to provide an antibacterial porous electrospun nanofiber and a preparation method thereof and application thereof in killing bacteria, viruses and fungi, so as to fill the gap in the prior art.

[0008] The antibacterial porous electrostatic spinning nanofiber provided by the present invention uses polymer material polyvinylidene fluoride or polyvinylidene fluoride co-hexafluoropropylene as the fiber body, and embeds porous hydrogen-bonded organic skeleton material monomer (nanocrystal) tetrakis(p-benzoic acid)pyrene or 1,3,6,8-tetrakis(2-fluoro-4-carboxyphenyl)pyrene to form a porous nano composite fiber material; the nano fiber material has porosity; the nano fiber material has high mechanical strength and good air permeability; the nano fiber material can generate singlet oxygen in situ under light conditions, and its singlet oxygen generation rate is twice that of hydrogen-bonded organic skeleton micron crystals; the nano fiber material can efficiently kill bacteria, viruses and fungi under light conditions.

[0009] The specific steps of preparing the antibacterial porous electrospun nanofibers provided by the present invention are as follows:

[0010] (1) Preparation of electrospinning precursor solution: disperse the polymer material and hydrogen-bonded organic framework material monomers in a certain proportion in N,N-dimethylformamide solution, stir for 1.5-2.5 hours (preferably 2 hours), and remove bubbles in the solution by ultrasonication for subsequent use;

[0011] (2) Preparation of porous electrospun nanofibers: The electrospinning precursor solution is transferred to the syringe of the electrospinning device and formed into fibers. The electrospinning voltage is 18-22 kV (preferably 20 kV) and the electrospinning distance is 12-16 cm (preferably 15 cm).

[0012] In the present invention, the content of hydrogen-bonded organic framework material in the porous electrospun nanofibers can be adjusted by changing the amount of hydrogen-bonded organic framework material monomers; specifically, the mass ratio of the polymer material to the hydrogen-bonded organic framework material monomers used is in the range of 100:0.5~100:10 (100:(0.5~10)), and the content of hydrogen-bonded organic framework material in the obtained porous electrospun nanofibers is 0.5 wt%~10 wt%.

[0013] In the present invention, the hydrogen-bonded organic framework material monomer is tetrakis(p-benzoic acid)pyrene or 1,3,6,8-tetrakis(2-fluoro-4-carboxyphenyl)pyrene.

[0014] In the present invention, the polymer material is polyvinylidene fluoride or polyvinylidene fluoride co-hexafluoropropylene.

[0015] In the present invention, the hydrogen-bonded organic skeleton material monomer used is tetrakis(p-terephthalate)pyrene, the polymer material is polyvinylidene fluoride, polyvinylidene fluoride co-hexafluoropropylene, and the obtained porous electrospun nanofibers are correspondingly recorded as HOF-101-H@PVDF and HOF-101-H@PVDF-HFP. The hydrogen-bonded organic skeleton material monomer used is 1,3,6,8-tetrakis(2-fluoro-4-carboxyphenyl)pyrene, the polymer material is polyvinylidene fluoride, polyvinylidene fluoride co-hexafluoropropylene, and the obtained porous electrospun nanofibers are correspondingly recorded as HOF-101-F@PVDF and HOF-101-F@PVDF-HFP.

[0016] The present invention prepares antibacterial porous electrospun nanofibers, which can control the content of hydrogen-bonded organic skeleton materials, have a porous structure, high mechanical strength, good air permeability, and excellent acid-base stability; they can generate singlet oxygen in situ under light conditions and kill bacteria, viruses and fungi under light conditions.

[0017] The antibacterial porous electrospun nanofibers prepared by the present invention can adjust the content of hydrogen-bonded organic skeleton materials and have a porous structure. Compared with pure hydrogen-bonded organic skeleton materials, the size of the hydrogen-bonded organic skeleton materials in the nanofibers is nanometer-sized, and light can be effectively used to generate singlet oxygen, thereby being able to efficiently kill bacteria, viruses and fungi. Specifically, for example, nanofibers can efficiently kill Escherichia coli. Compared with hydrogen-bonded organic skeleton antibacterial coatings under the same conditions, the killing rate of Escherichia coli is 50% higher. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a flow chart for preparing antibacterial porous electrospun nanofibers in Examples 1 to 7.

[0019] Figure 2 This is a physical picture of the HOF-101-H@PVDF-HFP nanofibers in Examples 1 to 4.

[0020] Figure 3 This is a scanning electron microscope image (SEM) of the HOF-101-H@PVDF-HFP nanofibers in Examples 1 to 4.

[0021] Figure 4 1 is the X-ray powder diffraction pattern (PXRD) of HOF-101-H@PVDF-HFP nanofibers in Examples 1 to 7.

[0022] Figure 5 This is the nitrogen adsorption curve of 10 wt% HOF-101-H@PVDF-HFP nanofibers in Example 1.

[0023] Figure 6 This is the infrared absorption spectrum of HOF-101-H@PVDF-HFP nanofibers in Examples 1 to 4.

[0024] Figure 7 This is a scanning electron microscope image (SEM) of the HOF-101-F@PVDF-HFP nanofibers in Examples 5 to 7.

[0025] Figure 8 This is the air permeability of 10 wt% HOF-101-H@PVDF-HFP nanofibers in Example 1.

[0026] Fig. 9 It is the tensile strength of HOF-101-H@PVDF-HFP nanofibers in Examples 1 and 4.

[0027] Fig.10 is the singlet oxygen yield of the antibacterial porous electrospun nanofibers in Example 8.

[0028] Fig.11 This is a diagram of the antibacterial effect of the material in Example 9.

[0029] Fig.12 It is the antibacterial rate of the material in Example 9.

[0030] Fig.13 It is the antiviral rate of the material in Example 10.

[0031] Fig.14 It is the antifungal rate of the material in Example 11.

[0032] Fig.15 This is the cytotoxicity of the material in Example 12. Implementation

[0033] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0034] Sources of main reagents: polyvinylidene fluoride and polyvinylidene fluoride co-hexafluoropropylene were purchased from Shanghai Titan Technology Co., Ltd.; 1,3,6,8-tetrakis(p-benzoic acid)pyrene and 1,3,6,8-tetrakis(2-fluoro-4-carboxyphenyl)pyrene were synthesized in the laboratory.

[0035] Example 1, preparation of 10 wt% HOF-101-H@PVDF-HFP nanofibers.

[0036] Preparation of 10 wt% HOF-101-H@PVDF-HFP nanofibers: 80 mg of 1,3,6,8-tetrakis(p-benzoic acid)pyrene and 800 mg of polyvinylidene fluoride co-hexafluoropropylene were dissolved in 5 ml of N,N-dimethylformamide. After complete dissolution, they were transferred to the syringe of the electrospinning equipment and made into fibers. The whole process used an electrospinning voltage of 20 kV and an electrospinning distance of 15 cm. The preparation process is as follows Figure 1 The actual sample of the prepared sample is shown in Figure 2 The scanning electron microscope (SEM) images of the prepared samples showed that the diameter of the 10 wt% HOF-101-H@PVDF-HFP nanofibers was approximately 200 nm ( Figure 3 ). 10 wt% HOF-101-H@PVDF-HFP nanofibers with hydrogen-bonded organic skeleton structure ( Figure 4 ) was verified by X-ray powder diffraction (PXRD). Nitrogen adsorption data ( Figure 5 ) shows that 10 wt% HOF-101-H@PVDF-HFP nanofibers have a porous structure. Infrared absorption spectrum ( Figure 6 ) shows that 10 wt% HOF-101-H@PVDF-HFP nanofibers have absorption peaks of two components, HOF-101-H and PVDF-HFP. Characterization of air permeability, the air permeability of HOF-101-H@PVDF-HFP nanofiber membranes was tested using a digital air permeability tester (YG461E / II) with a diameter of 20 cm and a pressure of 200 Pa ( Figure 8). For the characterization of tensile strength, the size of the HOF-101-H@PVDF-HFP nanofiber membrane was 6×2 cm2. The tensile test was performed on an Instron 5969 at a speed of 10.0 mm / min and a starting gauge length of 5 mm. The tensile strength of 10 wt% HOF-101-H@PVDF-HFP nanofiber was 2.8 MPa ( Fig. 9 ).

[0037] Example 2, preparation of 5 wt% HOF-101-H@PVDF-HFP nanofibers.

[0038] Preparation of 5 wt% HOF-101-H@PVDF-HFP nanofibers: 40 mg of 1,3,6,8-tetrakis(p-benzoic acid)pyrene and 800 mg of polyvinylidene fluoride co-hexafluoropropylene were dissolved in 5 ml of N,N-dimethylformamide. After complete dissolution, they were transferred to the syringe of the electrospinning equipment and made into fibers. The whole process used an electrospinning voltage of 20 kV and an electrospinning distance of 15 cm. The preparation process is as follows Figure 1 The actual sample of the prepared sample is shown in Figure 2 The scanning electron microscope (SEM) images of the prepared samples showed that the diameter of the 5 wt% HOF-101-H@PVDF-HFP nanofibers was approximately 200 nm ( Figure 3 ). 5 wt% Hydrogen bonded organic skeleton structure in HOF-101-H@PVDF-HFP nanofibers ( Figure 4 ) is verified by X-ray powder diffraction pattern (PXRD). Infrared absorption spectrum ( Figure 6 ) shows that HOF-101-H@PVDF-HFP nanofibers have absorption peaks of two components, HOF-101-H and PVDF-HFP.

[0039] Example 3, preparation of 1 wt% HOF-101-H@PVDF-HFP nanofibers.

[0040] Preparation of 1 wt% HOF-101-H@PVDF-HFP nanofibers: 8 mg of 1,3,6,8-tetrakis(p-benzoic acid)pyrene and 800 mg of polyvinylidene fluoride co-hexafluoropropylene were dissolved in 5 ml of N,N-dimethylformamide. After complete dissolution, they were transferred to the syringe of the electrospinning device and made into fibers. The entire process used an electrospinning voltage of 20 kV and an electrospinning distance of 15 cm. The preparation process is as follows Figure 1 The actual sample of the prepared sample is shown in Figure 2 The scanning electron microscope (SEM) images of the prepared samples showed that the diameter of the 1 wt% HOF-101-H@PVDF-HFP nanofibers was approximately 200 nm ( Figure 3 ). 1 wt% Hydrogen bonded organic skeleton structure in HOF-101-H@PVDF-HFP nanofibers ( Figure 4 ) is verified by X-ray powder diffraction pattern (PXRD). Infrared absorption spectrum ( Figure 6 ) shows that HOF-101-H@PVDF-HFP nanofibers have absorption peaks of two components, HOF-101-H and PVDF-HFP.

[0041] Example 4, preparation of 0.5 wt% HOF-101-H@PVDF-HFP nanofibers.

[0042] Preparation of 0.5 wt% HOF-101-H@PVDF-HFP nanofibers: 4 mg of 1,3,6,8-tetrakis(p-benzoic acid)pyrene and 800 mg of polyvinylidene fluoride co-hexafluoropropylene were dissolved in 5 ml of N,N-dimethylformamide. After complete dissolution, they were transferred to the syringe of the electrospinning equipment and made into fibers. The whole process used an electrospinning voltage of 20 kV and an electrospinning distance of 15 cm. The preparation process is as follows Figure 1 The actual sample of the prepared sample is shown in Figure 2 The scanning electron microscope (SEM) images of the prepared samples showed that the diameter of the 0.5 wt% HOF-101-H@PVDF-HFP nanofibers was approximately 200 nm ( Figure 3 ). 0.5 wt% HOF-101-H@PVDF-HFP nanofibers with hydrogen-bonded organic skeleton structure ( Figure 4 ) is verified by X-ray powder diffraction pattern (PXRD). Infrared absorption spectrum ( Figure 6 ) shows that HOF-101-H@PVDF-HFP nanofibers have absorption peaks of two components, HOF-101-H and PVDF-HFP. Characterization of tensile strength, the size of the HOF-101-H@PVDF-HFP nanofiber membrane is 6×2 square centimeters. The tensile test was carried out on Instron 5969 with a speed of 10.0 mm / min and a starting gauge length of 5 mm. The tensile strength of 10 wt% HOF-101-H@PVDF-HFP nanofibers is 8.5 MPa ( Fig. 9 ).

[0043] Example 5, preparation of 5 wt% HOF-101-F@PVDF-HFP nanofibers.

[0044] Preparation of 5 wt% HOF-101-F@PVDF-HFP nanofibers: 40 mg of 1,3,6,8-tetrakis(2-fluoro-4-carboxyphenyl)pyrene and 800 mg of polyvinylidene fluoride co-hexafluoropropylene were dissolved in 5 ml of N,N-dimethylformamide. After complete dissolution, they were transferred to the syringe of the electrospinning equipment and made into fibers. The entire process used an electrospinning voltage of 20 kV and an electrospinning distance of 15 cm. The preparation process is as follows: Figure 1 The scanning electron microscope (SEM) images of the prepared samples showed that the diameter of the 5 wt% HOF-101-F@PVDF-HFP nanofibers was approximately 200 nm ( Figure 7 ). 5 wt% Hydrogen bonded organic skeleton structure in HOF-101-F@PVDF-HFP nanofibers ( Figure 4 ) was verified by powder X-ray diffraction pattern (PXRD).

[0045] Example 6, preparation of 1 wt% HOF-101-F@PVDF-HFP nanofibers.

[0046] Preparation of 1 wt% HOF-101-F@PVDF-HFP nanofibers: 8 mg of 1,3,6,8-tetrakis(2-fluoro-4-carboxyphenyl)pyrene and 800 mg of polyvinylidene fluoride co-hexafluoropropylene were dissolved in 5 ml of N,N-dimethylformamide. After complete dissolution, they were transferred to the syringe of the electrospinning device and made into fibers. The entire process used an electrospinning voltage of 20 kV and an electrospinning distance of 15 cm. The preparation process is as follows Figure 1 The scanning electron microscope (SEM) images of the prepared samples showed that the diameter of the 5 wt% HOF-101-F@PVDF-HFP nanofibers was approximately 200 nm ( Figure 7 ). 5 wt% Hydrogen bonded organic skeleton structure in HOF-101-F@PVDF-HFP nanofibers ( Figure 4 ) was verified by powder X-ray diffraction pattern (PXRD).

[0047] Example 7, preparation of 0.5 wt% HOF-101-F@PVDF-HFP nanofibers.

[0048] Preparation of 0.5 wt% HOF-101-F@PVDF-HFP nanofibers: 4 mg of 1,3,6,8-tetrakis(2-fluoro-4-carboxyphenyl)pyrene and 800 mg of polyvinylidene fluoride co-hexafluoropropylene were dissolved in 5 ml of N,N-dimethylformamide. After complete dissolution, they were transferred to the syringe of the electrospinning equipment and made into fibers. The entire process used an electrospinning voltage of 20 kV and an electrospinning distance of 15 cm. The preparation process is as follows Figure 1The scanning electron microscope (SEM) images of the prepared samples showed that the diameter of the 5 wt% HOF-101-F@PVDF-HFP nanofibers was approximately 200 nm ( Figure 7 ). 5 wt% Hydrogen bonded organic skeleton structure in HOF-101-F@PVDF-HFP nanofibers ( Figure 4 ) was verified by powder X-ray diffraction pattern (PXRD).

[0049] Example 8, determination of singlet oxygen yield of porous electrospun nanofibers.

[0050] Experimental measurement of singlet oxygen yield: The yield of singlet oxygen yield was tested by bleaching 1,3-diphenylisobenzofuran. 20 mL of a solution of 1,3-diphenylisobenzofuran in methanol (200 mmol / L) was placed in a 30 mL quartz photocatalytic reactor. After adding HOF-101@PVDF-HFP nanofibers to the 1,3-diphenylisobenzofuran solution, the absorbance of 1,3-diphenylisobenzofuran did not change. It was then rapidly decomposed under green LED irradiation (10 W, 520 nm). The amount of singlet oxygen generated within 20 min, related to the decomposed 1,3-diphenylisobenzofuran in the solution, was calculated as the difference in absorbance at 410 nm before and after green LED irradiation. The mass of all HOF-101@PVDF-HFP nanofibers used for singlet oxygen generation experiments was 10 mg, and the electrospinning time was 1 h.

[0051] The singlet oxygen yield is Fig.10 As shown. It can be observed that within 20 minutes, the singlet oxygen yield of HOF-101@PVDF-HFP nanofibers is as follows: 0.5 wt% HOF-101-F@PVDF-HFP nanofibers>1 wt% HOF-101-F@PVDF-HFP nanofibers>0.5 wt% HOF-101-H@PVDF-HFP nanofibers>5 wt% HOF-101-F@PVDF-HFP nanofibers>1wt% HOF-101-H@PVDF-HFP nanofibers>5 wt% HOF-101-H@PVDF-HFP nanofibers.

[0052] Example 9, test on the sterilization rate of porous electrospun nanofibers.

[0053] Taking the HOF-101-F@PVDF-HFP prepared in the above embodiment as an example, the nanofibers were cut into a size of 0.5×0.5 square centimeters and placed in a 2 ml centrifuge tube. The centrifuge tube containing the HOF-101-F@PVDF-HFP nanofibers was placed on a clean bench, sealed with tin foil sprayed with 75% ethylene, and then dried overnight in a blast drying oven at 60°C. 10 μl of bacterial cryopreservation solution was added to 5 ml of bacterial culture medium, and then cultured in a shaker at 37°C and 250 rpm for 16 hours. Then 1.5 μl of bacterial suspension was evenly dropped on each group of nanofibers. The nanofibers covered with bacteria were placed under a desk lamp that had been preheated for 10 minutes, with a light intensity of about 1400 lux. After 2.5, 5 or 10 minutes of illumination, each group of samples was placed in a centrifuge tube (1.5 ml) containing 0.5 ml of sterile water. Then vortex at the highest speed for 10 seconds, and add 25 microliters of bacterial suspension to 975 microliters of sterile water. Spread 5 microliters of diluted bacterial suspension evenly on the bacterial culture agar plate and mark it. After culturing in a 37 ℃ constant temperature incubator for 11-12 hours, record the photos of each bacterial culture dish. Count the bacterial colonies, take the blank group as the control, and calculate the antibacterial rate of each group after different light exposure times.

[0054] Through the antibacterial effect diagram of the material ( Fig.11 ), it can be observed that within 5 minutes, HOF-101-F@PVDF-HFP nanofibers have a significant inactivation effect on bacteria. After statistics, it can be obtained that the antibacterial ability of HOF-101-F@PVDF-HFP nanofibers is 1 wt% HOF-101-F@PVDF-HFP nanofibers≈0.5 wt% HOF-101-F@PVDF-HFP nanofibers>5 wt% HOF-101-F@PVDF-HFP nanofibers ( Fig.12 ).

[0055] Example 10, test of antiviral rate of porous electrospun nanofibers.

[0056] Taking the HOF-101-F@PVDF-HFP prepared in the above example as an example, the nanofibers were cut into a size of 0.5×0.5 cm2 and placed in a 2 ml centrifuge tube. The centrifuge tube containing the HOF-101-F@PVDF-HFP nanofibers was placed on a clean bench, sealed with tin foil sprayed with 75% ethylene, and then dried in a 60°C forced air drying oven overnight. The virus titers of vesicular stomatitis virus (VSV) and herpes simplex virus type 1 (HSV-1) were measured using TCID 50 The data were expressed as PFU (plaque forming units). For each virus, 100 μl of culture medium (2.0 × 10 6PFU / ml) were evenly dropped on the surface of HOF-101-F@PVDF-HFP nanofibers. After different time (0, 5, 10, 20 min) of sunlight treatment, the nanofibers were washed with 100 μl of DMEM, and the virus was serially diluted at a dilution of 1:10. 100 μl of 10 -1 ~ 10 -8 After culturing for 4 to 5 days at 37°C and 5% CO2, each well was checked for cytopathic effects and the TCID was calculated using the Spearman-Karber method. 50 All t-test calculations were performed using GraphPad software (GraphPad Software, Inc.).

[0057] It can be observed that within 20 minutes, HOF-101-F@PVDF-HFP nanofibers have a significant inactivation effect on viruses. After statistics, it can be found that the antiviral ability of HOF-101-F@PVDF-HFP nanofibers is 0.5 wt% HOF-101-F@PVDF-HFP nanofibers>1 wt% HOF-101-F@PVDF-HFP nanofibers>5 wt% HOF-101-F@PVDF-HFP nanofibers ( Fig.13 ).

[0058] Example 11, test on antifungal efficiency of porous electrospun nanofibers.

[0059] Taking the HOF-101-F@PVDF-HFP prepared in Example 6 as an example, the nanofibers were cut into a size of 0.5×0.5 square centimeters and placed in a 2 ml centrifuge tube. The centrifuge tube containing the HOF-101-F@PVDF-HFP nanofibers was placed on a clean bench, sealed with tin foil sprayed with 75% ethylene, and then dried in a 60°C forced air drying oven overnight. Candida albicans SC5314 strain (C. albicans fungus) or Candida albicans 819 strain (C. auris fungus) was cultured overnight at 30°C in YPD (2% glucose, 1% yeast extract, 2% peptone) liquid culture medium. The fungal strain was washed three times with 1 ml of phosphate-buffered saline, resuspended in 5 ml of phosphate-buffered saline, and the concentration was adjusted to 1×10 8CFU / mL. In a sterile culture dish, 1.5 μL of fungal suspension was evenly dropped on the nanofibers, followed by light treatment for different times (2.5, 5, or 10 minutes). Each group of nanofibers was then washed with 0.5 mL of phosphate-buffered saline and vortexed at maximum speed for 10 seconds. The residual diphtheria strains at the bottom of the culture dish were washed and collected with 0.5 mL of phosphate-buffered saline. A total of 10 μL of the diluted fungal suspension was evenly plated on YPD solid medium. After incubation at 30°C for 24 hours, the plates were photographed and the CFUs were counted. The fungal infection rate was calculated by subtracting the CFU number of the light-treated group from the CFU number of the control group and dividing it by the CFU number of the control group.

[0060] It can be observed that within 10 minutes, HOF-101-F@PVDF-HFP nanofibers have a significant inhibitory effect on fungi ( Fig.14 ).

[0061] The HOF-101-H@PVDF-HFP prepared in Example 1-4 also has good bactericidal, antiviral and antifungal effects, the details of which are omitted.

[0062] Example 12, determination of cytotoxicity.

[0063] Take HOF-101-F@PVDF-HFP prepared in Example 7 as an example. The cytotoxicity of HOF-101-F@PVDF-HFP nanofibers was studied using the cell counting kit-8 (CCK8) assay. Human epidermal keratinocytes-adult (HEKa, 5000 cells per well) were cultured overnight in a 96-well plate. The cells were treated with HOF-101-F@PVDF-HFP nanofibers of different sizes (0.50 cm2, 0.25 cm2, 0.125 cm2, 0.0625 cm2, 0.03125 cm2) for 5 minutes, and distinguished whether there was light (1400 LUX). The cells were further cultured for 48 hours, stained with CCK8 solution for 1 hour, and the absorbance was measured at 450 nm. The calculation method for cell viability is as follows:

[0064] .

[0065] It can be observed that the survival rate of human epidermal keratinocytes is above 90% regardless of whether there is light exposure, indicating that the material has no cytotoxicity and good biocompatibility ( Fig.15 ).

[0066] Considering the flexibility and high mechanical stability of nanofiber materials, these materials have the potential to become important materials for constructing bacterial protection equipment in the future.

Claims

1. A method for preparing antibacterial porous electrospun nanofibers, characterized in that: The specific steps are as follows: (1) Preparation of electrospinning precursor solution: Disperse polymer materials and hydrogen-bonded organic framework material monomers in N,N-dimethylformamide solution, stir for 1.5-2.5 hours, and remove bubbles in the solution by ultrasonication for subsequent use; (2) Preparation of porous electrospun nanofibers: The electrospinning precursor solution was transferred into the syringe of the electrospinning device and formed into fibers. The electrospinning voltage was 18-22 kV and the electrospinning distance was 12-16 cm. The content of hydrogen-bonded organic framework material in the porous electrospun nanofibers can be adjusted by changing the amount of hydrogen-bonded organic framework material monomers; specifically, the mass ratio of the polymer material to the hydrogen-bonded organic framework material monomers is 100:0.5-100:10, and the content of hydrogen-bonded organic framework material in the porous electrospun nanofibers is 0.5 wt%-10 wt%; The hydrogen-bonded organic framework material monomer is tetrakis(p-benzoic acid)pyrene or 1,3,6,8-tetrakis(2-fluoro-4-carboxyphenyl)pyrene; The polymer material is polyvinylidene fluoride or polyvinylidene fluoride co-hexafluoropropylene.

2. The preparation method according to claim 1, characterized in that: The monomer of the hydrogen-bonded organic skeleton material is tetrakis(p-terephthalate)pyrene, the polymer material is polyvinylidene fluoride, polyvinylidene fluoride co-hexafluoropropylene, and the obtained porous electrospun nanofibers are recorded as HOF-101-H@PVDF and HOF-101-H@PVDF-HFP; the monomer of the hydrogen-bonded organic skeleton material is 1,3,6,8-tetrakis(2-fluoro-4-carboxyphenyl)pyrene, the polymer material is polyvinylidene fluoride, polyvinylidene fluoride co-hexafluoropropylene, and the obtained porous electrospun nanofibers are recorded as HOF-101-F@PVDF and HOF-101-F@PVDF-HFP.

3. An antibacterial porous electrospun nanofiber obtained by the preparation method according to claim 1 or 2.

4. Use of the antibacterial porous electrospun nanofibers as claimed in claim 3 in killing bacteria, viruses and fungi.

Citation Information

Patent Citations

  • Preparation method of antibacterial metal organic framework composite nanofiber

    CN105854853A